Brain mechanisms mediating effects of stress on reward sensitivity. (August 2018) - Ironside, Maria; Kumar, Poornima; Kang, Min-Su; Pizzagalli, Diego A
Highlights: Stress preferentially perturbates reward anticipation (rather than consumption). Cortico–striatal–limbic network dysregulation subserves stress effects on reward. Probing functional connectivity may allow greater cross-species integration. Stress effects on opioid receptors may uncover novel treatment targets. Abstract : Acute and chronic stress have dissociable effects on reward sensitivity, and a better understanding of these effects promises to elucidate the pathophysiology of stress-related disorders, particularly depression. Recent preclinical and human findings suggest that stress particularly affects reward anticipation; chronic stress perturbates dopamine signaling in the medial prefrontal cortex and ventral striatum; and such effects are further moderated by early adversities. Additionally, a systems-level approach is uncovering the interplay among striatal, limbic and control networks giving rise to stress-related, blunted reward sensitivity. Together, this cross-species confluence has not only enriched our understanding of stress-reward links but also highlighted the role of neuropeptides and opioid receptors in such effects, and thereby identified novel targets for stress-related neuropsychiatric disorders.